Risk of death from breast cancer after treatment for ductal carcinoma in situ. Issue 11 (22nd August 2017) - Wadsten, C; Garmo, H; Fredriksson, I; Sund, M; Wärnberg, F
Abstract: Background: Studies to date have failed to demonstrate any survival benefit from preventing local recurrence after treatment for ductal breast carcinoma in situ (DCIS). Patient- and tumour-related risk factors for death from breast cancer in women with a primary DCIS were analysed here in a large case–control study. Methods: A nested case–control study was conducted in a population-based cohort of women with primary DCIS between 1992 and 2012. Women who later died from breast cancer were identified. Four controls per case were selected randomly by incidence density sampling. Medical records and pathology reports were retrieved. Conditional logistic regression was used to calculate odds ratios (ORs) and 95 per cent confidence intervals for risk of death from breast cancer. Results: From a cohort of 6964 women, 96 who died from breast cancer were identified and these were compared with a group of 318 controls. Tumour size over 25 mm or multifocal DCIS (OR 2·55, 95 per cent c.i. 1·53 to 4·25), a positive or uncertain margin status (OR 3·91, 1·59 to 9·61) and detection outside the screening programme (OR 2·12, 1·16 to 3·86) increased the risk of death from breast cancer. The risks were not affected by age or type of treatment. In the multivariable analysis, tumour size (OR 1·95, 1·06 to 3·67) and margin status (OR 2·69, 1·15 to 7·11) remained significant. Conclusion: In the present study, large tumour size and positive or uncertain margin status were associated with a higher risk of death from breast cancer after treatment for primary DCIS. More extensive treatment was not associated with lower risk, which may be due to confounding by indication, or indicate that some DCIS has an inherent potential for metastatic spread. Abstract : Rare, but worse for large tumours and uncertain margins